PERHITUNGAN TINGKAT RETURN SAHAM BURSA EFEK INDONESIA DENGAN METODE CAPITAL ASSET PRICE MODEL (CAPM) - Syahib Natarsyah (SEKOLAH TINGGI ILMU EKONOMI NASIONAL (STIENAS) BANJARMASIN, 2016)
Abstract, This research aims to conduct standardized testing Capital Asset Pricing Model (CAPM) at the Indonesian Stock Exchange (BEI) in the period January 2016 to in June 2016. The data analysis technique used is the closing price of the monthly average for 6 months is incorporated in LQ-45, JSX Composite and the Interest rate SBI regression method that First and Second Pass regression. Results First Pass Regression is known that beta average of 1.257 with Std.Error Of The Estimate of 6.588%. Then the results of Second-Pass Regression is known that Y = -0.751 + [0.261 * Beta] + [0.427 * Std.Se]. Results of tests performed it has been found that simultaneous two independent variables (beta and Std.Error Estimates) has a significant effect where F arithmetic = 6.596 with a significance level with probability < 0.05, with the contribution of the effect is very small, only 0.047% (R-Square). Partial test showed only variable significantly Std.Error of Estimate with a regression coefficient of 0.427 (t-hit = 3.533 with siginifikansi level p < 0.05), where as beta variable is not significant. Furthermore, to prove whether the standard CAPM is valid in the Indonesia Stock Exchange, conducted testing on the estimation Second-Pass Regression in accordance with the rules that have been determined. The results of the analysis carried out has been known that the standard CAPM seems not apply in the Indonesia Stock Exchange least for such period identified in this research, so the CAPM method can not be fully used to predict accurately the level of stock returns in the Indonesia stock Exchange.